Application of Pregnant Exercise and Hypnosis Techniques As Effort to Improve Health in Pregnant Mothers Trimester III - Pakpahan, Sulastry; Panggabean, Hetty (Green Publisher Indonesia, 2022)
Pregnancy exercise is one of the sports that can be done by pregnant women in the third trimester . Pregnancy can cause worry and anxiety in pregnant women, making them vulnerable to mental and psychological disorders . Severe anxiety during pregnancy can cause changes in blood flow to the baby, so that the flow of oxygen and other important nutrients to the baby's organs is disrupted . The purpose of this study was to analyze efforts to improve health in pregnant women. This study used a field method with pre-test and post-test techniques to determine the increase in participants ' knowledge about pregnancy exercise and hypnosis techniques. The results of this study indicate that community service activities What is done can be well received by pregnant women in the third trimester as a target. Pregnant women seemed very enthusiastic about participating in this activity and based on the results of the posttest given there was an increase in the mother's understanding and knowledge about pregnancy exercise and hypnosis techniques. This is also an effort to improve maternal health during pregnancy, especially in the third trimester of pregnancy to prepare for a safe and easy delivery.